IMPLEMENTATION OF LEARNING STRATEGIES FOR IMPROVING COMMUNICATION SKILLS - Khaerudin Khaerudin (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
This research aims (1). To find out the learning process in improving Communication skills (2). To find out good results and achievements (3). To know the learning process. The research method uses a qualitative approach by carrying out learning strategies, learning strategies, and Communication skills strategies, including listening skills, speaking skills, reading skills, and writing skills. Data collection techniques (1) Conduct interviews with school principals and their representatives, Communication teachers, and students. (2). Survey the location to observe the phenomena that occur in the location (3). Study documentation in the form of archives, USB, files, and important meeting notes. To complement the existing data. Conclusion all aspects of skills play an important role in the learning process in improving Communication skills. Factors in improving learning include: listening skill strategies, Communication skills, listening skills, reading skills, speaking skills, and writing skills